Perceived self-efficacy, cultural values, and coping styles among Chinese families of children with autism. Issue 2 (2nd April 2016) - Huang, Mary; Zhou, Zheng
Abstract : Autism spectrum disorder (ASD) is a pervasive developmental disorder that has grown in prevalence over the past few decades and has a tremendous impact on families that struggle with adjustment to this disorder. Initial exposure to such a disorder may be a significant source of stress and tribulation for Chinese families who are not accustomed to mental health discourse and related services in the health arena and surrounding community. Little is known of how Chinese parents cope when raising children with ASD. The purpose of this study was to gain an in-depth understanding of ways that Chinese families cope with stress when they have a child diagnosed with ASD. Seven Chinese families with children between the ages of 2 and 5 who were diagnosed with ASD participated in this qualitative study. Results may guide assessment and intervention for professionals who work with Chinese families within clinical, school, health, and community settings. Thematic analyses explored factors contributing to parental stress, perceived parenting self-efficacy, and parents' adherence to traditional Asian values, patterns of coping, and overall satisfaction with the early intervention (EI) services that their children are receiving. Implications for practices in school psychology and future directions are also discussed.